Ez-argue: empowering students to master the art of argumentative writing - Azim@Nik Azim, Nik Ahmad Farhan; Hussein, Nur Hafezah; Abdullah, Arifuddin; Amiruddin, Ahmad Zaki; Omar, Suhaida (Universiti Teknologi MARA, Kedah, 2023)
The development of written argumentation in academic settings has been slow and is often characterized by subpar quality. Criticisms of argumentation rhetoric and its patterns highlight the prevalence of fallacies in argumentative writing. Numerous studies have identified the root of this problem as a complex interplay between linguistic, sociocultural, and cognitive factors. Additionally, Covid-19 pandemic has introduced challenges to the teaching and learning of argumentative writing; necessitating modifications in instructional design and approaches to address the intricacies of argumentative writing. In response to the pressing concerns, many instructors have turned to technology as a mean to bridge the pedagogical gap, particularly in the realm of academic writing practices. This study proposes the utilization of EZ-Argue, a technology-mediated tool designed to support students in their practice of argumentative essay writing. Specifically targeting weak and average students, EZ-Argue models functional words, phrases, and sentence patterns that are pertinent to argumentative genre. A textual analysis of 167 argumentative essay scripts were carried out to examine the impact of EZ-Argue as a treatment on student’s writing and the delivery of argumentative writing instructions. The findings indicated most frequent errors were found at formation of thesis statement, counterargument, and refutation. The analysis also revealed a positive outlook of these three elements when EZ-Argue was used as a treatment. Pedagogically, the findings of this study were expected to provide valuable insights to instructors informing them about the potential and effectiveness of employing such a tool in facilitating argumentative writing instructions.